A systematic review of the literature on the surgical management of recurrent rectal prolapse. (August 2015) - Hotouras, A.; Ribas, Y.; Zakeri, S.; Bhan, C.; Wexner, S. D.; Chan, C. L.; Murphy, J.
Abstract Aim There are no available guidelines to support surgical decision‐making in recurrent rectal prolapse. This systematic review evaluated the results of abdominal or perineal surgery for recurrent rectal prolapse, with the aim of developing an evidence‐based treatment algorithm. Method PubMed and MEDLINE databases were searched for all clinical studies involving patients who underwent surgery for recurrent rectal prolapse between 1950 and 2014. The primary outcome measure was the recurrence rate after abdominal or perineal surgery for recurrent rectal prolapse. Secondary outcomes included morbidity, mortality and quality of life data where available. Results There were no randomized controlled studies comparing the success rates of abdominal or perineal surgery for recurrent rectal prolapse. Most studies were heterogeneous, of low quality (level IV) and involved small numbers of patients. The follow‐up of 144 patients included in the studies undergoing perineal surgery ranged from 8.8 to 81 months, with recurrence rates varying from 0% to 50%. Morbidity ranged from 0% to 17% with no mortality reported. Limited data on quality of life following the Altemeier procedure were available. The follow‐up for 158 patients included in the studies who underwent abdominal surgery ranged from 0 to 23 years, during which recurrence rates varied from 0% to 15%. Morbidity rates ranged from 0% to 32% with 4% mortality. No quality of life data were available for patients undergoing abdominal surgery. Conclusion This systematic review was unable to develop a treatment algorithm for recurrent rectal prolapse due to the variety of surgical techniques described and the low level of evidence within heterogeneous studies. Larger high‐quality studies are necessary to guide practice in this difficult area.